IMPLEMENTING MODERN METHODS IN HUMAN RESOURCE DEVELOPMENT AND MANAGEMENT - Xusanov Xasanjon (Лучшие интеллектуальные исследования, 2024)
Annotation: In the strategy of actions for the further development of the Republic of Uzbekistan, the priority tasks were the radical improvement of the educational sphere, improving the quality of education, the formation of a generation of intellectual potential, physical perfection, deepening the exact sciences and training qualified personnel for various sectors of the economy, and ultimately the creation of an educational system that